Java programs to accompany programming logic and design - Smith, Jo Ann. (Australia : Course Technology Cengage Learning, 2013)
An experienced industry practitioner -- she has directed a computer training company in the Chicago area and worked for nine years at AT&T Bell Laboratories -- Jo Ann Smith is currently a computer consultant in higher education. Ms. Smith previously served as Assistant Professor of Computer Information Systems at Harper College in Palatine, Illinois, and taught at the College of DuPage in Glen Ellyn, Illinois, and at the University of St. Francis in Joliet, Illinois. JAVA$1!" (BPROGRAMS TO ACCOMPANY PROGRAMMING LOGIC AND DESIGN is specifically designed to be paired with the latest edition of Farrell's highly successful PROGRAMMING LOGIC AND DESIGN. Together, the two books provide the perfect opportunity for those who want to learn the fundamentals of logic as well as the basics of an actual programming language. Readers discover how real C++ code functions while still mastering concepts and taking advantage of the strengths of a traditional language-independent logic and design course.s